Effect of KMnO4 Concentration Variation and Gelatinization Temperature on the Physical Characteristics and Bioplastic Active Packaging Effectiveness - Lestari, Kadek Irma Dwi; Yulianti, Ni Luh; Gunadnya, Ida Bagus Putu Gunadnya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Active packaging involves incorporating active compounds or ingredients into packaging films that can affect the packaged product. Potassium permanganate (KMnO₄) is a compound with strong oxidizing properties against ethylene gas produced by climacteric fruits. In the manufacture of bioplastics, gelatinization temperature can affect the physical characteristics of active bioplastic packaging, as this process begins with the swelling of starch granules due to water absorption during heating. This study aimed to determine the effect of KMnO₄ concentration and gelatinization temperature on the physical characteristics of bioplastics and the effectiveness of packaging on avocado fruit quality during a 10-day shelf life. A two-factorial completely randomized design (RBD) was used, with KMnO₄ concentration levels of 10%, 15%, and 20%, and gelatinization temperatures of 70°C and 75°C. The results showed that active bioplastic packaging influenced the effectiveness of absorbing ethylene gas in avocados during 10 days of storage. Interaction between treatments significantly affected tensile strength, elongation, elasticity, water absorption, weight loss, texture, and total dissolved solids. The best treatment for physical characteristics was 10% KMnO₄ and 75°C gelatinization (K1S2), resulting in a tensile strength of 34.43 MPa, elongation of 4.49%, elasticity of 795.88 MPa, and water absorption of 0.71%, which also affected avocado quality during 10-day storage with weight loss of 2.43%, texture of 87.43 N, and total dissolved solids of 4.4 °Brix.